Efforts to Improve Nurses Performance Through the Value and Frequency of Infection Prevention and Control Training at Haji Hospital, East Java Province: Upaya Peningkatan Kinerja Perawat Melalui Nilai dan Frekuensi Pelatihan Pencegahan dan Pengendalian Infeksi di RSUD Haji Provinsi Jawa Timur - Chafifah Tri Nuraini; Anif Prasetyorini (Bachelor of Hospital Administration, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
In 2023, as man as 14.81% of nurses at the RSUD Haji didn’t pass infection prevention and control training with a standart of 100%. The purpose of this research is influence of the value of infection prevention and control training and frequency of training on the performance of nurses at the RSUD Haji. This research method uses a questionnaire with a total sampling of 27 respondents from nurses at the RSUD Haji, with a quantitative research type and a cross-sectional research design. The results of this research include descriptive analysis and logistic regression tests. Where the results of the data analysis show that the value of infection prevention and control training (0.038 < 0.05) and the frequency of training (0.020 < 0.05) influence the performance of nurses at the RSUD Haji. Meanwhile, the variables age, length of service and level of education have no effect on the performance of nurses at the RSUD Haji. The training frequency variable is proven to have a significant influence on improving nurse performance. Suggestions that need are holding internal training and other health seminars.